PSYCHOLOGICAL ANALYSIS OF THE PROBLEM OF WOMEN'S SOCIAL ACTIVITY IN THE CONTEXT OF FAMILY STABILITY - Harutyunyan, Narine (Modern Psychology, 2022)
The article is devoted to problem of the social role, status and activity of a modern woman. Since the middle of 20th century the problem became the subject of research in the context of family stability in which the main role was given to the spouse’s vision of woman’s social activity. The social activity is considered as an external function of family and includes social, political, educational, professional orientation, intellectual merits, skills and abilities, i.e. the activity of spouses outside the family. It gives the satisfaction of needs that are practically impossible to meet within the family.We have studied the hierarchy of family values ​​from the aspect of stability and the ways of expectations and ambitions of 120 families (women-men, n = 240) during the implementation of functions, their relevance within the economic, parenting, social activity, emotional spheres and in external attractiveness. The results of the research allow us to consider the equal distribution of responsibilities of social activity of the spouses as the main precondition for family stability.  According to research results, the relatively high rate of social activity of a person/spouse in a system of value hierarchy proves that this function is one of the important factors for strengthening and stabilizing the family relationships.
Keywords: social activity; family stability; family functions; social role; status